Land Suitability of Agricultural Crops for Supporting Peat Restoration In South Kalimantan, Indonesia - Abdul Hadi; Muhammad Syarbini; Maria Sari L. Panjaitan (Journal of Wetlands Environmental Management, 2019)
Following the release of Presidential Regulation No 1/2016, a peat restoration pilot project has been carried out in Banjarbaru District, South Kalimantan in addition to other two pilot projects in other provinces of Indonesia. The pilot project has been designed to implement the three aspects of peat restoration, namely rewetting, revegetation and revitalization of society.Â  Implementation of revegetation is mainly through applying agroforestry by growing agricultural crops in spaces between trees. The objective of present study was to elucidate the suitability of agricultural crops in area of restoration of degraded peatland in South Kalimantan, Indonesia. The suitability of agricultural crops was studied by collecting rainfall and air temperature data from the climatic station of Syamsudin Noor Airport in Banjarbaru, while the nutrient retentions values were determined in the laboratory. Peat depth and drainage class were determined by direct field observations, while peat decomposition level was classified by quantitative method in the field. All collected data were then used to assess the land suitability class forÂ  dry land paddy (Oriza sativa L), long bean (Vigna sinensis ENDL), cucumber (Cucumis sativus LINN), mustard (Brassica rugose FRAIN), orange (Citrus sp), stink bean (Parkia speciose HASSK), rubber (Hevea brassialiansis M.A), and coconut (Cocus nocifera L). The productivity data of long bean, cucumber and mustard were obtained by farmer interview. The results showed that most of the agricultural crops were classified as marginally suitable (Class S3).The main limiting factors of agricultural development in this area are low soil pH, low base saturation and peat ripening. Peat depth limits the development of some crops. The above mentioned limiting factors ought to contribute to the low crop productivities in the area. The limiting factors were less severe for pineapple and stink bean, indicating that these crops have potential to be grown along with trees for restoration efforts in the area.